A robust approach for highly transparent Y2O3 ceramics by stabilizing oxygen defects. (August 2017) - Jung, Wook Ki; Ma, Ho Jin; Park, Youngtae; Kim, Do Kyung
Abstract: Highly transparent Y2 O3 ceramics were fabricated suppressing the formation of oxygen vacancies during vacuum sintering for the first time. Oxygen stabilization in transparent Y2 O3 ceramics was successfully enabled by additional ZrO2 oxygen source considering thermodynamics. The oxygen-stabilized ceramics approached nearly theoretical transmittance without further post-annealing and hot isostatic presssing. This new approach is potentially applicable for the fabrication of other transparent ceramics. Graphical abstract: Oxygen stabilization in transparent Y2 O3 ceramics is successfully enabled during vacuum sintering by additional ZrO2 oxygen source. The oxygen-stabilized ceramics shows nearly theoretical transmittance without further post-annealing and HIP procedure. This new approach is potentially applicable for the fabrication of other transparent ceramics.